Perlindungan Hukum Terhadap Data Pribadi Dalam Sistem Informasi Publik (International Forum of Researchers and Lecturers, 2025)
Legal protection of personal data in public information systems is an important aspect of maintaining individual privacy in the digital era. This journal examines various regulations governing personal data protection, including the Personal Data Protection Law and other related policies. This research uses a qualitative approach with case study analysis on several public agencies in Indonesia. The results show that despite the legal framework, the implementation of personal data protection still faces various challenges, such as a lack of understanding among public employees and a lack of socialization of individual rights. This study recommends the need for awareness raising and training for public agencies as well as strengthening supervisory mechanisms to ensure more effective personal data protection.